2018
DOI: 10.3389/fimmu.2018.02348
|View full text |Cite
|
Sign up to set email alerts
|

2D Kinetic Analysis of TCR and CD8 Coreceptor for LCMV GP33 Epitopes

Abstract: The LCMV GP33 CD8 epitope has long been one of the most widely used antigens in viral immunology. Of note, almost all of the in vitro analyses of CD8 T cell responses to this epitope make use of an altered peptide ligand (APL) in which the cysteine from the original 9-mer peptide (KAVYNFATC) is substituted by a methionine at position 41 (KAVYNFATM). In addition, it is possible that the antigen processed during natural LCMV infection is an 11-mer peptide (KAVYNFATCGI) rather than the widely used 9-mer. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 87 publications
(118 reference statements)
4
43
0
Order By: Relevance
“…This is consistent with a pioneer study made with atomic force microscopy, revealing that CD8 was not increasing adhesion efficiency for an activating peptide in a mouse system (Puech 2011). This may however seem at variance with recent reports that CD8 might increase the lifetime of TCR/pMHC interactions (Kolawole 2018, Hong 2018. However, while it seems well demonstrated that T cell activation may enhance the stability of the interaction between TCR born by CD8+ cells and cognate pMHCs (O'Rourke 1990, Hong 2018, Kolawole 2018, it is not clear whether this phenomenon can occur during the first seconds following initial TCR engagement.…”
Section: Adhesion Experimentssupporting
confidence: 90%
See 2 more Smart Citations
“…This is consistent with a pioneer study made with atomic force microscopy, revealing that CD8 was not increasing adhesion efficiency for an activating peptide in a mouse system (Puech 2011). This may however seem at variance with recent reports that CD8 might increase the lifetime of TCR/pMHC interactions (Kolawole 2018, Hong 2018. However, while it seems well demonstrated that T cell activation may enhance the stability of the interaction between TCR born by CD8+ cells and cognate pMHCs (O'Rourke 1990, Hong 2018, Kolawole 2018, it is not clear whether this phenomenon can occur during the first seconds following initial TCR engagement.…”
Section: Adhesion Experimentssupporting
confidence: 90%
“…This may however seem at variance with recent reports that CD8 might increase the lifetime of TCR/pMHC interactions (Kolawole 2018, Hong 2018. However, while it seems well demonstrated that T cell activation may enhance the stability of the interaction between TCR born by CD8+ cells and cognate pMHCs (O'Rourke 1990, Hong 2018, Kolawole 2018, it is not clear whether this phenomenon can occur during the first seconds following initial TCR engagement. Also, the effect of CD8 on TCR-pMHC interaction was reported to depend on tested TCR (Zhong 2013).…”
Section: Adhesion Experimentsmentioning
confidence: 56%
See 1 more Smart Citation
“…There is no doubt that catch bonds can be detected with the flow chamber (9, 39), including by our group (40). Forming catch bonds at 10 to 15 pN has been proposed to increase ligand discrimination by strongly increasing differences in bond lifetimes between catch bond forming agonists peptides and slip bond-forming irrelevant or antagonist peptides (19)(20)(21)(22). Using the laminar flow chamber, nonspecific TCR-pMHC interactions could not be detected here, and so presumably had lifetimes shorter than the detection threshold of 180 ms.…”
Section: Discussion What Is the Physiological Relevance Of Single Tcrmentioning
confidence: 99%
“…For these reasons, efforts have been made to measure TCR-pMHC 2D dissociation kinetics and the effect of mechanical force thereon. Independent studies using the biomembrane force probe (BFP) (19)(20)(21)(22) or optical tweezers (23) on live cells, or using optical tweezers in cell-free experimental setup (23,24) reported that activating TCR-pMHC interactions exhibit a decrease in off-rate when exposed to mechanical force in the 10-to 15-pN range, i.e., catch bonds. It was therefore suggested that T cells might probe the TCR-pMHC bond by exerting a pull on the order of 10 pN, with activating peptides displaying a nonintuitive increase bond lifetime that made it 10-fold higher than the lifetime of nonactivating peptides (19).…”
mentioning
confidence: 99%